A Bioadhesive Barrier-Forming Oral Liquid Gel Improved Oral Mucositis and Nutritional Status in Patients With Head and Neck Cancers Undergoing Radiotherapy: A Retrospective Single Center Study - Wei, Jinlong; Wu, Jie; Wang, Huanhuan; Wang, Bin; Zhao, Tingting; Meng, Lingbin; Dong, Lihua; Jiang, Xin (Frontiers in Oncology, 2021)
Background Episil® is a bioadhesive barrier-forming oral liquid gel that can relieve oral mucositis (OM) caused by radiotherapy (RT) and hence relieves pain effectively. In this study, we observed the effects of Episil® on the OM and nutritional status of patients with head and neck cancers (HNCs) undergoing RT. Methods A total of 50 HNC patients were divided into the Episil® (25 patients) and control (25 patients) groups. Patients in the Episil® group were sprayed with Episil®. In the control group, the kangfuxin solution or Kangsu™ oral gargle was used. Medical staff assessed the OM extent and timing as well as the nutritional status during treatment and recorded adverse reactions other than OM. The nutritional status assessment included the following indicators: Patient Generated-Subjective Global Assessment (PG-SGA) score, body mass index (BMI), body weight, albumin levels, and other hematological indicators. Results The incidence of high-level OM (III–IV) after RT was lower in the Episil® group than in the control group (P < 0.05). Nutritional status assessments showed that the Episil® group had a lower percentage of weight loss than the control group at weeks 4 and 7 after RT. Similar results were also obtained for BMI and albumin levels (P < 0.05). Moreover, according to PG-SGA scores, fewer patients in the Episil® group were malnourished and more patients were well-nourished (P < 0.05) compared with the control group. Conclusion Episil® effectively improved OM and malnutrition in HNC patients who received RT and has a good clinical application value.